Teologi Tubuh Perspektif Paus Fransiskus bagi Penghayatan Kaul Kemurnian Para Religius Perempuan - Prihartanti, Marcellina; Andalas, Mutiara (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2025)
Chaste women who follow religious vows face new difficulties in the digital age. How does Pope Francis rethink the theology of the body in light of interactions with modern realities and technological advancements? This study presents Pope Francis's groundbreaking view of contemporary theology of the body. The comprehensive examination of papers released by Pope Francis reveals the progressive and all-encompassing perspective of the Pope about spirituality, technology, and sexuality. The study's findings demonstrate that, in addition to acknowledging the challenges presented by the digital age, Pope Francis also proposes creative ways to reconcile theological knowledge with technological advancements. He emphasizes the value of a well-rounded education that includes sexual, psychological, and spiritual facets. The Pope also stresses the importance of having frank conversations about sexuality and using digital media responsibly. Pope Francis's contribution to the process of sexuality formation is this renewal, which seeks to assist religious women live out their vocations faithfully in the digital age by forming a healthy and balanced awareness of the body and sexuality.AbstrakEra digital membawa tantangan baru bagi religius perempuan yang menghayati kaul kemurnian. Berdasarkan perjumpaan dengan realitas kontemporer dan kemajuan teknologi, bagaimana Paus Fransiskus membaharui pandangan tentang teologi tubuh? Penelitan ini mengungkapkan perspektif revolusioner Paus Fransiskus tentang teologi tubuh di zaman modern. Melalui analisis mendalam terhadap dokumen – dokumen yang dikeluarkan oleh Paus Fransiskus, mengungkapkan pendekatan holistik dan progresif Paus terhadap seksualitas, spiritualitas dan teknologi. Hasil penelitian menunjukkan bahwa Paus Fransiskus tidak hanya mengakui kompleksitas era digital, melainkan juga menawarkan solusi inovatif untuk mengintegrasikan pemahaman teologis dengan realitas digital. Beliau menyoroti pentingnya formasi yang holistik, mencakup aspek spiritual, psikologis, dan seksual. Paus Fransiskus juga menekankan perlunya dialog terbuka tentang seksualitas hingga penggunaan secara bijak media digital. Pembaharuan ini menjadi kontribusi Paus Fransiskus terhadap proses formatio seksualitas, yang bertujuan untuk membentuk pemahaman yang sehat dan terintegrasi tentang tubuh dan seksualitas dikalangan religius perempuan dan membantu mereka menghayati kesetiaan panggilan mereka pada era digital.